"Sollte sich die Einstellung des Personals gegenüber den Patienten nicht ändern, garantiere ich für nichts mehr!": Protestmännlichkeit und KrankheitsbewäItigung von "aufsässigen Patienten" der Psychiatrischen Universitätskinik Heidelberg am Vorabend der Psychiatriereform = "Should the staff's attitude towards the patients remain unchanged, I will not guarantee anything." Protest masculinity and coping of "rebellious patients" at the Heidelberg University Psychiatric Hospital on the eve of deinstitutionalization - Schwamm, Christoph (Medizinhistorisches Journal, 2015)
This article analyses the illness experiences of male patients from the Heidelberg University Psychiatric Hospital during the protests against Psychiatry in the year 1973. Protest is one of the most important expressions of masculinity in socially disadvantaged men, such as men with mental disorders. The analysis of 100 medical records shows that some patients tried to construct themselves as men in a way that was explicitly motivated by antipsychiatric ideas: They questioned psychiatric authority, behaved "sexually inappropriate", or used drugs. On the eve of psychiatric reform in West Germany those patients were well aware that the alternative--complying with the treatment--would put them at considerable risk. In addition to the usual inference of hegemonic or normative masculinities as risk-factors, the behavior of those ,,rebellious patients" has to be interpreted as individual coping strategies.